Peningkatan Ketersediaan dan Penjualan Produk Pada Usaha Rumahan Bakso Mamita - I Made Bhaskara Gautama; I Made Mika Parwita; Dewa Bagus Satya Mahottama; I Putu Ananta Kusumadewa (Indonesian Journal Publisher, 2025)
Frozen food is a popular preservation method nowadays. The main benefits of frozen food include extending shelf life, reducing waste, and maintaining nutritional value as well as the quality of taste and texture. Meatballs are an example of popular frozen food. A major advantage of frozen meatballs is the convenience of storage, allowing access at any time without worrying about quality deterioration. One business that produces frozen meatballs is Bakso Mamita, a small-scale home industry with limited capacity. They rely on a Pre Order (PO) system due to limited stock and equipment. Some customers are sometimes unwilling to wait for the PO process, causing this business to often lose potential customers. The ability of this business to provide or stock goods needs to be improved to grow. Moreover, if the stock issue can be resolved, this business also needs to enhance sales or marketing so that the stored products sell well. Activities were carried out by providing assistance in the form of a freezer to increase the availability of goods. In addition, digital marketing and content creation training were provided to boost sales from the increased availability of goods. Based on the evaluation results, the availability of goods in this business increased by 1233%, with sales increasing by 111.84%. Digital marketing and digital content training activities increased partners' basic understanding by an average of 76.5%.